Implementation of standardized cystic fibrosis care algorithm to improve the center data-quality improvement project international collaboration - ERDEM ERALP, ELA (My University, 2023)
Background: A collaboration between the University of Michigan (U of M) Cystic Fibrosis Center (CFC) and Marmara University (MU) CFC was initiated to improve the health status of people with cystic fibrosis (pwCF) at MU through implementing Quality Improvement (QI) initiatives. The main aim was to improve lung function in children with FEV1pp <80. The secondary aim was to assess the changes in health related quality of life. Methods: Included in the project were pwCF who received cystic fibrosis (CF) care at the MU CFC and were 6–18 years of age with an FEV1pp <80. Flow charts were created and a standardized CF care algorithm was implemented. Weekly case review were done to develop individualized treatment plans. Appropriate intervention was applied and patient data were assessed at baseline, 3, 6, 9 and 12 months. The Cystic Fibrosis Revised Questionnaire (CFQ-R) was completed. Results: 55 pwCF were included (mean age:11.8 ± 3.3 years). Mean FEV1pp (SD) at baseline, 6 and 12 month was 63.7 (14.6), 66.9 (16.6), 70.4 (19.2), respectively, with a relative increase of 5.0% in 6 months (p:0.002) and 10.5% in 12 months compared to baseline (p<0.001). Physical functioning, eating problems and respiratory symptoms domains of the CFQ-R questionnaire were improved at the end of the one year for 6–13 (p = 0.024, p = 0.009, p = 0.002) and 13–18 year olds (p = 0.013, p = 0.002, p = 0.038). Conclusion: There was significant improvement in pwCF with FEV1<80%pp after implementing this QI project. The processes and assessments used can be adopted by other low-middle income countries to improve similar measures.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Akciğer ve Solunum Tıbbı; Pediatrics, Perinatology and Child Health; Pulmonary and Respiratory Medicine; Children; Cystic fibrosis; Lung function; Quality improvement; Lung function; Quality improvement; Cystic fibrosis; Children